Pluralisme Agama dan Toleransi dalam Islamic Wordview - Hasanah, Amalia; Mujahid, Kasori (Lembaga Yasin AlSys, 2024)
Understanding the differences is not something easy. To do so requires a spaciousness of heart in understanding the difference. If the difference is only due to physical factors, then it is still easy to understand. However, if the difference is related to religious beliefs and beliefs, it is certainly not easy. How should one understand that there are beliefs that he considers to be heretical or forbidden teachings and that these teachings must be tolerated because of human factors. Religion has always taught absolute truths that cannot be negotiable. Every religion teaches about that absolute truth. The truth of Islam is absolute. So are other religions. So when each religion teaches absolute truth, it is very likely that conflicts will occur due to the absolution of the teachings of their respective religions. To understand the difference, there is only one fundamental thing, namely that man was created by Allah Almighty. in diversity. Understanding differences thus does not mean putting these differences in a container and melting into one, but there are still differences, we must realize that differences are not to be eliminated but used as partners to strengthen each other. So by understanding that differences do not have to be eliminated, then we have actually worked to understand those differences and make them a strength to work together.